Determinantes del tipo de cambio real en el Perú: 2002 - 2016 - Huamanchumo Luis, Erick Javier (2018)
The present research work was carried out with the objective of determining the main variables that explain the behavior of the Real Exchange Rate (RER) in Peru and the magnitude of its influence of these variables, during the years of 2002 to 2016. In this research, quarterly data from the RER, productivity, terms of trade, government spending, capital flows and commercial openness were used; obtained from the Central Reserve Bank of Peru, National Institute of Statistics and Informatics and the International Monetary Fund. An error correction vector (VEC) model is estimated to determine the long-term relationship between the TCR and its main explanatory variables (determinants). The results establish a negative relationship between productivity, a negative relationship between the terms of trade, a negative relationship between government spending, a positive relationship with the flow of capital and a positive relationship between trade openness. Likewise, it is verified through the econometric model that all the coefficients of the explanatory variables of the estimated model are individually significant, at 95% confidence, complemented by the presence of global significance at 95% confidence.